High Order Thinking Skills (HOTS) Analysis of Grade VIII Junior High School Students on the Subject of Preserving My Nation's Culture - Anilawati, Anilawati; Jatiningsih, Oksiana; Listyaningsih, Listyaningsih (IKIP Widya Darma Surabaya, 2025)
Objective: This study aims to analyze the higher-order thinking skills (HOTS) of students of State Junior High School 15 Surabaya. in understanding and applying the material